Technological and economic analyses on power generation from the waste heat in a modified aluminum smeltingpot. (28th December 2019) - Pan, Qiang; Zhao, Ruijie; Jiang, Qifeng; Gosselin, Louis
Summary: Current pot ventilation system is designed in a conservative manner to prevent hazardous gases from escaping aluminum smelting pots. Reduction of pot draft is an initiative of both efficiently using waste heat in the exhaust gas and significantly reducing fan power of the ventilation system. This work presents a systematic analysis on the reduction of pot draft and the consequent problem, ie, fugitive emissions from the smelting pot. Numerical models with different length scales are developed to simulate the fluid flow and heat transfer in pots and potroom. The superstructure of a typical aluminum smelting pot is successfully modified to maintain the pot tightness in the reducing pot draft. The results show that the current pot draft could be reduced by 50% at least using the developed technology. The techno‐economic analysis of power generation from the waste heat in aluminum smelting pot is made based on organic Rankine cycle (ORC), and the potential benefits of using the pot exhaust gas of both normal and 50% reduced flow rates are estimated. It is found that the levelized energy cost of the optimized ORC system using 50% reduced exhaust gas is 0.048 $/kWh with a system's lifespan of 10 years and 0.038 $/kWh with a lifespan of 15 years while the payback time of investment is 5.2 years. Abstract : A modification of the pot superstructure is proposed to enhance the pot tightness, especially for the working condition of reducing pot draft, and the result is validated by the CFD simulations. The potentially economic value of waste heat in 50% reduced pot exhaust gas is estimated based on a specific ORC power generation. Compared with the normal pot draft, the system LEC and payback time of investment are both reduced to an acceptable level.